Prospective clinical study of enamel wear caused by monolithic zirconia resin-bonded inlay-retained and wing-retained fixed partial dentures over 5 years - Bömicke, Wolfgang; Haas, Julius; Awounvo Awounvo, Junior Sinclair; Rammelsberg, Peter; Rues, Stefan (Clinical oral investigations, 2025)
Objectives: To prospectively evaluate the wear of posterior zirconia resin-bonded fixed partial dentures (RBFPDs) with polished occlusal surfaces and their natural enamel antagonists compared to contralateral controls in an enamel-enamel contact over 5 years. Materials and methods: In six patients with either an inlay- or wing-retained RBFPD made of monolithic 3 mol% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP), wear was evaluated indirectly using baseline and annual polyvinyl siloxane impressions. Resulting gypsum models were digitized and aligned by unchanged surface areas. Wear was analyzed by depth and area. For each parameter, descriptive statistics were used to express the degree of wear observed at yearly intervals for each group. A linear mixed regression analysis was performed to compare the enamel opposing 3Y-TZP group and the enamel-enamel controls at tooth level. All statistical tests were conducted at the 5% significance level. Results: After 5 years, the mean enamel wear depth of teeth opposing 3Y-TZP was 77 μm, compared to 54 μm for control teeth. No wear was observed on the 3Y-TZP RBFPDs. Maximum enamel wear depth and wear area were 229 μm and 9 mm², respectively, for teeth opposing 3Y-TZP, and 135 μm and 5 mm² for control teeth. Significant differences in mean enamel wear depth emerged after 2 years of observation. Conclusions: Polished 3Y-TZP caused more enamel wear than natural antagonists over 5 years, but the wear remained within the range reported for other commonly used indirect restorative materials. Clinical relevance: The clinical use of polished 3Y-TZP restorations appears to be justified in terms of natural antagonist wear behavior.